Reflection on the implementation of Decision on Implementation of Article 66.2 of the TRIPS Agreement: Incentive for technology transfer to least-developed countries - Jessyca van Weelde; Xiaoping Wu; Ting-Wei (Alex) Chiang; Bassam Peter Khazin (World Trade Organization (WTO), 2023)
Technology transfer is deeply embedded in the WTO Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement). Several provisions address technology transfer, which constitute an essential part of the efforts made by the TRIPS negotiators to strike a balance between the advancement of technological innovation and the promotion of transfer and dissemination of technology. Article 66.2 specifically obligates developed country Members to provide incentives to enterprises and institutions in their territories to promote and encourage technology transfer to least-developed country (LDC) Members in order to enable them to create a sound and viable technological base. This paper summarizes the WTO TRIPS Council's work on the implementation of Article 66.2 from 2018 to 2020, including the implementation of a reporting mechanism for developed country Members' programmes established by the TRIPS Council and the TRIPS Council's review of the ensuing reports, and annual Workshops convened to enhance practical dialogue on technology transfer under this provision. In particular, it provides an analytical review of 708 programmes broken down into seven categories of technology, namely agriculture and food; environment and climate change; information and communication technology (ICT); public health and pharmaceuticals; intellectual property; business, trade and finance; and education and social sciences. The paper also reports on a survey of LDC Members which identified as priority areas for technology transfer as agriculture and food; environment and climate change; ICT; and public health and pharmaceuticals. The paper concludes by drawing on lessons learned from the past 25 years' experiences and reflecting on prospects for future work.
Keywords: F13; O3; O31; O34; O38; 330; technology transfer; LDCs; Article 66.2; TRIPS; incentives; agriculture; environment; public health; ICT; SDGs; knowledge transfer